Rethinking the social role of nursing through the work of Donzelot and Foucault - Evy Nazon; Amelie Peron; Thomas Foth (York University Libraries, 2019)
The history of nursing is often perceived as the history of a profession with charitable and philanthropic objectives of helping others live a healthy life. Many historians have celebrated the major role played by charitable women in nursing. Moving beyond this charitable and dedicated image of nurses, we argue that nursing, through "the social," became a pivotal component of the governance of the everyday lives of populations. As such, nursing became part of the evolving idea that all areas of life must be managed through a process of normalization that seeks to maximize the life of both the individual and the population. Populations thus became the focus of governmental projects. Jacques Donzelot's notion of invention of the social and Michel Foucault's concept of govenmentality make possible a reassessment of the conventional image of nurses, and in particular, that of charitable nurses.